The features of modern business culture of Japan (Journal of Oriental Studies, 2018)
In the given article were investigated the features of modern business culture of Japan. The uniquenessof Japanese culture is explained through historical peculiarities of development, height density ofpopulation, driven by geographical position and specific of Japanese language. Cultural and historicalvalues which influence on business culture of Japan were analyzed. Authors came to conclusion thatdisability of Japanese people to exchange and adopt elements from other culture, while preserving thenational cultural heritage by their own, strengthened in them a sense of of their own exclusivity. Japanesebusiness ethics is inextricably linked with the culture of the country and the ethnopsychology ofthe Japanese people.